The Conditions for Implementation of Innovative Activity of The Teacher - Nargiza Rustamovna Abdukakharova (Peerian Journals Publishing, 2023)
Changing the position and role of the teacher in the information society, the decrease in the quality of professional training, the need to develop new methods and ways of acquiring the teaching profession, the modernization of pedagogical education leads to a structural and substantive change of the pedagogical education system in our country. First, it was manifested in the formation of an updated image of a modern teacher - a universal professional, a professional mobile, able not only to carry out high-quality training on the subject, but also to learn independently, to master new subject areas and methods of action, ready to communicate effectively with various participants of the educational process.
Keywords: innovation; innovative activity; modern teacher; education system